An overview of survey-based research carried out with Australian preservice teachers (1995–2015). (April 2017) - Stephenson, Jennifer
Abstract: Teacher preparation in Australia is, as in other countries, a frequent topic of discussion and inquiries. This paper provides an overview of survey-based research, published in refereed journals from 1995 to 2015 where Australian preservice teachers were the respondents. The findings of the study were that commonly the surveys were small-scale with respondents most likely to be elementary school preservice teachers. Most surveys addressed attitudes, perceptions or beliefs and less frequently skills and knowledge. The reporting of many surveys was poor. There was a dearth of surveys recruiting from more than two universities, and hence a lack of meaningful comparisons of courses that could inform policy direction. Highlights: 304 surveys of Australian preservice teachers Australia published 1995–2015 are reviewed. Surveys were mostly small-scale, with few studies comparing programs. Surveys mostly addressed attitudes, perceptions and beliefs rather than skills or knowledge. Generally reporting of surveys was poor. Teacher educators in Australia need to be more open to comparative studies.